2022
DOI: 10.3350/cmh.2021.0236
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness study of universal screening for hepatitis C virus infection in South Korea: A societal perspective

Abstract: Background/Aims: This study aimed to evaluate the cost-effectiveness of hepatitis C virus (HCV) screening compared to no screening in the Korean population from societal and healthcare system perspectives.Methods: A published decision-tree plus Markov model was used to compare the expected costs and quality-adjusted life years (QALY) between one-time universal HCV screening and no screening in the population aged 40–65 years using the National Health Examination (NHE) program. Input parameters were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Recent work has shown that in the era of DAA therapy, universal onetime screening for HCV is also cost-effective [11,12]. ere is, however, a lack of Australian data and there is no cost analysis of testing OB patients, though we observe they could be accessed systematically in the emergency department (ED).…”
Section: Introductionmentioning
confidence: 86%
“…Recent work has shown that in the era of DAA therapy, universal onetime screening for HCV is also cost-effective [11,12]. ere is, however, a lack of Australian data and there is no cost analysis of testing OB patients, though we observe they could be accessed systematically in the emergency department (ED).…”
Section: Introductionmentioning
confidence: 86%
“…This suboptimal diagnosis rate for HCV infection is consistently observed in many studies, underscoring the importance of increased screening and surveillance for unidentified HCV infections 3–5 . In this regard, some countries and societies have adopted universal screening for HCV infection, and numerous efforts have been made to raise awareness about HCV infection and reduce barriers impeding access to the HCV care system 6–11 …”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the sixth most common cancer with 10% of cases originating from HCV infection in Korea [2]. The rising disease burden of HCV infection also reinforces the goal of the World Health Organization to eradicate HCV infection by 2030 [3] and thereby warrants the need to implement the universal national HCV screening for early diagnosis and implementation of optimal HCV infection treatment [4].…”
Section: Introductionmentioning
confidence: 99%